Masters of the Narrative: Culture and Power in Global Media’s Take on Palestine-Israel Conflict - Meranti, Meranti; Isa, Danto Erfantoro; Silviana, Isna (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
The study explores how major international media outlets craft and convey narratives, with a focus on Al Jazeera, BBC, and CNN. Grounded in Edward Said's